On a pair of fuzzy dominated mappings on closed ball in the multiplicative metric space with applications - Rasham, Tahair; Shabbir, Muhammad Sajjad; Agarwal, Praveen; Momani, Shaher (Fuzzy sets and systems, 2022)
The purpose of this paper is to establish some fixed point results for a pair of fuzzy dominated mappings satisfying contractive conditions on closed ball in multiplicative metric space. Some new fixed point results with graphic contraction on closed ball for a pair of fuzzy graph dominated mappings on multiplicative metric space have been established. Furthermore, we find a unique common solution for a system of non linear Voltera type integral equations and lastly we give an application to ensure the existence of common bounded solution of a functional equation in dynamic programming.